Formulation and physical stability of syrup containing gaharu (Aquilaria microcarpa Baill.) leaves extract - Mia Fitriana; Wawan Halwany; Yuni Kartika; Khoerul Anwar; Siswadi Siswadi; Muhammad Ikhwan Rizki; Beny Rahmanto; Susy Andriani (Jurnal Riset Industri Hasil Hutan, 2022)
One of natural ingredients that has potential as herbal medicines is the leaves of agarwood-producing plants.  Opportunities for the development of agarwood-producing plants (Aquilaria microcrocarpa Baill.) as medicinal plants are still wide open. Ethanol extract of Aquilaria microcarpa Baill folium extract was made in the form of syrup preparations to facilitate use. This study aimed to formulate Gaharu folium extract into syrup preparations. The syrup preparations were made into 3 formulas with variations in the concentration of sorbitol as a sweetener, namely 60%; 63% and 65%. The three formulas were then evaluated including organoleptic test, viscosity test, pH test, homogeneity test and specific gravity test. The hedonic test was also carried out to determine which formula was the most preferred. The evaluation results showed that all syrup formulas met a good range of syrup requirements. From the results of the analysis of the preference test data, it could be concluded that all formulas had a level of acceptance that was not significantly different, but formula 2 had the highest total hedonic score compared to other formulas. Formula 2 also had the appropriate pH, viscosity and specific gravity as a syrup.